Analisis Kecelakaan Kerja di PT. XYZ dengan Menggunakan Metode Job Safety Analysis - Al Aqsa, Ucha; Andivas, Marulan; Ismail Kurnia, Wahyu (SURYA TEKNIKA, 2024)
PT. XYZ is a company engaged in the field of fabrication, particularly in cutting. At PT. XYZ, there is currently no specific program to reduce workplace accidents. The cutting division at PT. XYZ frequently experiences workplace accidents. Therefore, the aim of this research is to reduce the potential for workplace accidents by using Job Safety Analysis. The data collection techniques employed are observation, interviews, and documentation. Data processing and analysis use the principles of Job Safety Analysis and Fishbone tools. Based on the research results, it was found that there are five hazard categories: extreme, high, moderate, and low. There is one hazard at the extreme level: being struck by chips from the cutting activity. The high level consists of one hazard: being struck by cutting blade fragments. The moderate level has one hazard: material not matching capacity. The low level includes three hazards: slipping, being struck by falling material, and being hit by sparks. The proposed prevention measure is elimination, where the source of workplace hazards in the cutting process is completely removed. The second step, substitution, involves replacing tools or materials with ones that meet the standards in the cutting process. The third step, engineering controls, includes installing warning signs. The fourth step, administrative controls, involves preparing safety meetings before starting work and close supervision. The fifth step is using appropriate personal protective equipment (PPE).